Cardiac Derived CD51-Positive Mesenchymal Stem Cells Enhance the Cardiac Repair Through SCF-Mediated Angiogenesis in Mice With Myocardial Infarction - Xie, Dong Mei; Chen, Yang; Liao, Yan; Lin, Wanwen; Dai, Gang; Lu, Di Han; Zhu, Shuanghua; Yang, Ke; Wu, Bingyuan; Chen, Zhihong; Peng, Chaoquan; Jiang, Mei Hua (Frontiers in Cell and Developmental Biology, 2021)
Objective: Many tissues contained resident mesenchymal stromal/stem cells (MSCs) that facilitated to tissue hemostasis and repair. However, there is no typical marker to identify the resident cardiac MSCs. We aimed to determine if CD51 could be used as a marker of cardiac MSCs and assess their therapeutic potential for acute myocardial infarction (AMI) in mice. Methods: Cardiac derived CD51+ CD31-CD45-Ter119- cells (named CD51+MSCs) were isolated from C57BL/6 mice(7-day-old) by flow cytometry. The CD51+MSCs cells were characterized by proliferation capacity, multi-differentiation potential, and expression of typical MSCs-related markers. Adult C57BL/6 mice (12-week-old) were utilized for AMI model via permanently ligating the left anterior descending coronary artery. The therapeutic efficacy of CD51+MSCs were estimated by echocardiography and pathological staining. To determine the underlying mechanism, lentiviruses were utilized to knockdown the selected stem cell factor (SCF) gene in CD51+MSCs. Results: In this study, CD51 was expressed in the entire layers of the cardiac wall in mice, including endocardium, epicardium and myocardium, and its expression decreased with age. Importantly, the cardiac CD51+MSCs possessed potent self-renewal potential and multi-lineage differentiation capacity in vitro, also expressed typical MSCs-related surface proteins. Furthermore, CD51+ MSCs transplantation significantly improves cardiac function and attenuated cardiac fibrosis through pro-angiogenesis activity after myocardial infarction in mice. Moreover, stem cell factor (SCF) secreted by CD51+ MSCs played an important role in angiogenesis of endothelial cells both in vivo and in vitro. Conclusions: Collectively, CD51 is a novel marker of cardiac resident MSCs, and CD51+MSCs therapy enhance the cardiac repair through SCF-mediated angiogenesis, which make CD51+MSCs the ideal source for cell-based therapy to ischemic heart disease.